Developing Optimal Approaches for Investigating Corruption Crimes in Unique Circumstances - Willy Naresta Hanum; Iswantoro, Iswantoro (Jurnal Justice Dialectical, 2024)
Investigating criminal acts of corruption in certain circumstances is ineffective because the investigation and prosecution process carried out by law enforcement officials in Indonesia is discontinuous. This is normative legal research that uses a statutory approach to determine material and formal suitability for investigating criminal acts of corruption in certain circumstances. The legal materials used are primary and secondary. The data collection technique was carried out by literature study and then analyzed using the syllogism method. The research results show, first, that the lack of optimal investigation is influenced by three factors: substance, structure, and legal culture. Second, formulating ideals for investigating criminal acts of corruption in specific circumstances is necessary. This includes revising the provisions on criminal threats in court decisions, reformulating the role and function of the police, prosecutors, and corruption eradication commissions related to investigations, and recognizing the community's role in preventing corruption in Indonesia. Therefore, the government must consider reformulating the investigation of criminal acts of corruption, especially in certain circumstances, to make it more effective.